The Cauchy Problem of the Hartree Equation (Journal of Partial Differential Equations, 2008)
In this paper, we systematically study the wellposedness, illposedness of the Hartree equation, and obtain the sharp local wellposedness, the global existence in H^s, s ≥ 1 and the small scattering result in H^s for 2 < γ < n and s ≥ \frac{γ}{2}-1. In addition, we study the nonexistence of nontrivial asymptotically free solutions of the Hartree equation.
Keywords: Hartree equation; well-posedness; illposedness; Galilean invariance; dispersion analysis; scattering; asymptotically free solutions